Manajemen Pelayanan Kesehatan di Pondok Pesantren Attanwir Bojonegoro Jawa Timur - Siti Fatimatul Fajriyah; Fahrurrozi; Baqiyatush Sholihah (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2021)
In education management, health service management is part of special service management. Disease problems that continue to exist and are often experienced by santri of pesantren, especially attanwir pesantren are scabies (scabies), itching, shortness of breath, fever, fainting, cough, runny nose, mild pain, and ulcers. RSKLSM Attanwir is a health clinic that was established to help improve health and welfare as well as improve the healthy life of pesantren residents. RSLKSM operational activities involve students who are members of Santri Siaga with the vision of "care for social and humanity". The types of health services provided by RSLKSM are carried out by combining the traditional thibbun nabawi health methods with conventional methods. This study aims to describe the planning, implementation, and evaluation of health services and the implications of health service management on health services at Pondok Pesantren Attanwir Bojonegoro. This research uses descriptive qualitative field research with the triangulation technique. The results obtained indicate that each stage in the implementation of service management is multi-faceted, namely comprehensive, integrated, in-depth, and detailed. The nature of multi-faceted services can be found in health service activities, one of which is in the implementation of mass cupping activities.